TAX HAVEN COUNTRIES AND THEIR RELATIONSHIP TO INTERNATIONAL TAX EVASION (World Bulletin of Management and Law, 2023)
The first appearance of tax havens was associated with attracting foreign investments, but they have become one of the most important mechanisms for international tax evasion in the current era, by enabling negative practices of individuals and companies, which costs the global tax system a loss of 724 billion dollars annually, 74.64% of the total losses. Therefore, this study came to shed light on this phenomenon, which has witnessed a significant expansion in recent years, and to urge the establishment of international strategies to limit its expansion.